Directed synthesis of bio-inorganic vanadium oxide composites using genetically modified filamentous phage - Mueller, Michael; Baik, Seungyun; Jeon, Hojeong; Kim, Yuchan; Kim, Jungtae; Kim, Young Jun (Elsevier BV, 2015)
The growth of crystalline vanadium oxide using a filamentous bacteriophage template was investigated using sequential incubation in a V2O5 precursor. Using the genetic modification of the bacteriophage, we displayed two cysteines that constrained the RSTB-1 peptide on the major coat protein P8, resulting in vanadium oxide crystallization. The phage-driven vanadium oxide crystals with different topologies, microstructures, photodegradation and vanadium oxide composites were characterized by scanning electron microscopy (SEM), transmission electron microscopy (TEM), quartz microbalance and dissipation(QCM-D) and X-ray photoelectron spectroscopy (XPS). Non-specific electrostatic attraction between awild-type phage (wt-phage) and vanadium cations in the V2O5 precursor caused phage agglomeration and fiber formation along the length of the viral scaffold. As a result, the addition of recombinant phage(re-phage) in V2O5 precursors formed heterogeneous structures, which led to efficient condensation of vanadium oxide crystal formation in lines, shown by QCM-D analysis. Furthermore, re-phage/VxOx composites showed significantly enhanced photodegradation activities compared with the synthesized-wt-phage-V2O5 composite under illumination. This study demonstrates that peptide-mediated vanadium oxide mineralization is governed by a complicated interplay of peptide sequence, local structure, kinetics and the presence of a mineralizing aid, such as the two cysteine-constrained peptides on the phage surface, and has potential for use in nanotechnology applications. (C) 2015 Elsevier B.V. All rights reserved.